Implementation of Total Quality Management (TQM) for Enhancing Educational Quality: A Case Study of SMK Negeri 1 Buntok, Indonesia - Dwi Septian; Khairunnisa Khairunnisa; Khairatunnisa Khairatunnisa; Rida Maulidia; Aslamiah Aslamiah; Celia Cinantya (Universitas Negeri Malang, 2026)
Abstract: Improving the quality of education has become a strategic priority in developing competitive, adaptive, and high-quality human resources in the global era. In the context of vocational education, the demand for graduates’ relevance to labor market needs further emphasizes the importance of an effective and sustainable quality management system. Total Quality Management (TQM) is a managerial approach that focuses on continuous improvement through the active involvement of all organizational members. However, the implementation of TQM in vocational schools, particularly in regional contexts, still faces various contextual challenges that have not been extensively explored. Therefore, this study aims to analyze the implementation of TQM in improving educational quality at SMK Negeri 1 Buntok and to identify its supporting and inhibiting factors. This study employed a qualitative approach using a case study design. Data were collected through observations, in-depth interviews, and document analysis involving the principal, teachers, administrative staff, and school committee as key informants. Data analysis was conducted interactively through data reduction, data display, and conclusion drawing to obtain a comprehensive and contextual understanding. The findings reveal that the implementation of TQM at SMK Negeri 1 Buntok has been carried out systematically and integrated into the eight National Education Standards. The principal plays a crucial role as a key driver in fostering a quality culture through transformational, collaborative, and data-driven leadership. In addition, active participation of school members and community support serve as key enabling factors. However, several challenges remain, including the mismatch between teachers’ competencies and their teaching assignments, as well as the uneven understanding of TQM concepts among educators. This study contributes empirically to the enrichment of TQM literature in vocational education, particularly in regional contexts, and highlights that successful TQM implementation is determined by the synergy between leadership, organizational culture, and human resource readiness. Keywords: education quality improvement; integrated quality management; total quality management; vocational school